12-Month peak alpha frequency is a correlate but not a longitudinal predictor of non-verbal cognitive abilities in infants at low and high risk for autism spectrum disorder. (April 2021) - Carter Leno, Virginia; Pickles, Andrew; van Noordt, Stefon; Huberty, Scott; Desjardins, James; Webb, Sara Jane; Elsabbagh, Mayada; ,
Highlights: Peak alpha frequency (PAF) is thought to be a more sensitive and reliable measure of alpha band oscillatory activity. Higher PAF has been associated with better performance on a range of cognitive tasks. This study examines associations between PAF and non-verbal and verbal cognitive development in young infants aged 12–36 months. Abstract: Although studies of PAF in individuals with autism spectrum disorder (ASD) report group differences and associations with non-verbal cognitive ability, it is not known how PAF relates to familial risk for ASD, and whether similar associations with cognition in are present in infancy. Using a large multi-site prospective longitudinal dataset of infants with low and high familial risk for ASD, metrics of PAF at 12 months were extracted and growth curves estimated for cognitive development between 12–36 months. Analyses tested whether PAF 1) differs between low and high risk infants, 2) is associated with concurrent non-verbal/verbal cognitive ability and 3) predicts developmental change in non-verbal/verbal ability. Moderation of associations between PAF and cognitive ability by familial risk status was also tested. No differences in 12-month PAF were found between low and high risk infants. PAF was associated with concurrent non-verbal cognitive ability, but did not predict change in non-verbal cognitive over development. No associations were found between PAF and verbal ability, along with no evidence of moderation. PAF is not related to familial risk for ASD, and is a neural marker of concurrent non-verbal cognitive ability, but not verbal ability, in young infants at low and high risk for ASD